Vpliv ravnanja z zaposlenimi in organizacijske kulture na prilagodljivost poslovanja slovenskih lesnoindustrijskih podjetij - Kropivšek, Jože (Zbornik gozdarstva in lesarstva, 2003)
Human resources management and organizational culture have a significant impact on assuring adapted and adaptable business operations due to (changeable) environment. This fact is also evident in (Slovenian) wood-industry firms. Theoretically, this impact is associated with knowledge, which is in practice closely linked with innovativeness, exploitation of the employees' s abilities, their training and with relationships between employees in the firms. Thus, the theoretical analysis in this article shows (needed) organizational changes in discussed topics as a result of many changes in the environment. Many such changes were found which, however, are not equally important. In view of some deficiencies established in Slovenian wood industry firms with the aid of the opinion pool method, we have indicated possible solutions for the current situation in those firms. This wasone of the main objectives of the carried out research.
Keywords: lesna industrija; organizacija poslovanja; organizacijska kultura; zaposleni